2002
DOI: 10.1007/bf03032626
|View full text |Cite
|
Sign up to set email alerts
|

Urgent off-pump coronary artery bypass grafting

Abstract: Urgent off-pump CABG is safe and provides early recovery, provided that the patient's intraoperative hemodynamics are taken into account.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 19 publications
(17 reference statements)
0
10
0
Order By: Relevance
“…Furthermore, high heterogeneity in terms of operative risk between the intervention groups resulting from selection bias was expected given that choice of surgical technique was based on surgeon preference rather than a strict criterion. Interestingly, the majority of studies reported no significant difference between preoperative risk (determined by EuroSCORE, cardiogenic shock, preoperative IABP, ejection fraction, renal function), whereas four studies reported higher preoperative risk in the control group 17,24,25,43 and three studies reported vice versa. 6,8,10 However, in these studies in which there was a higher preoperative risk in the OPCAB or OnBHCAB group, there were marginally better or similar short and intermediate term results compared to ONCAB.…”
Section: Limitations and Strengthsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, high heterogeneity in terms of operative risk between the intervention groups resulting from selection bias was expected given that choice of surgical technique was based on surgeon preference rather than a strict criterion. Interestingly, the majority of studies reported no significant difference between preoperative risk (determined by EuroSCORE, cardiogenic shock, preoperative IABP, ejection fraction, renal function), whereas four studies reported higher preoperative risk in the control group 17,24,25,43 and three studies reported vice versa. 6,8,10 However, in these studies in which there was a higher preoperative risk in the OPCAB or OnBHCAB group, there were marginally better or similar short and intermediate term results compared to ONCAB.…”
Section: Limitations and Strengthsmentioning
confidence: 99%
“…A subgroup NMA looking at a higher acuity patient population was also performed. Nine studies 5,6,9,10,[24][25][26]31,32 assessing only patients with acute myocardial infarction (AMI) requiring emergency coronary revascularisation were identified.…”
Section: Primary Outcomementioning
confidence: 99%
“…Nonelective off-pump CABG was associated with comparable operative mortality and stroke rates with conventional on-pump CABG, echoing previous studies. 10,11 Previously, we demonstrated a decreased incidence of operative mortality and stroke after off-pump CABG compared with that after on-pump CABG in a risk-adjusted population. 6,18 Failure to achieve statistical significance might be attributed to the relatively smaller number of patients analyzed in this report.…”
Section: Outcomes Of Nonelective Off-pump Cabg Compared With Those Of On-pump Cabgmentioning
confidence: 99%
“…[5][6][7][8] However, there are few reports and comparative studies on outcomes with off-pump CABG in urgent and emergent cases versus the conventional approach with cardiopulmonary bypass. 9,10 Patients who undergo emergent or urgent CABG pose a greater challenge in terms of intraoperative and postoperative mortality and morbidity. Off-pump CABG might benefit these high-risk patients by eliminating the cardiopulmonary bypass and therefore decreasing the systemic inflammatory response associated with it.…”
mentioning
confidence: 99%
See 1 more Smart Citation